Syndecan-1 as a predictor of vulnerable atherosclerotic plaques - Qiu, Yan; Ouyang, Zhi; Zhong, Jian; Jin, Linlu; Qin, Yixue; Zeng, Ye (Frontiers in Cell and Developmental Biology, 2024)
Aims Cardiovascular disease remains a major global health concern, with atherosclerosis (AS) being a significant contributor. Vulnerable plaques play a critical role in acute cardiovascular events. Syndecan-1 (SDC-1), a vital membrane proteoglycan in the vascular endothelial glycocalyx, is believed to be associated with plaque progression. However, its precise relationship with severity and vulnerability of atherosclerotic plaque remains unclear. This study aimed to investigate SDC-1 expression and its potential correlation with plaque vulnerability in ApoE−/− atherosclerosis mouse model. Methods and results Eight-week-old mice were induced into the AS model using a high-fat diet (HFD) and/or partial ligation of the left common carotid artery (PLCA), with a chow diet (CD) control group. After 16 weeks, plaques in the aortic root showed the following order: HFD + PLCA group > HFD group > CD + PLCA group > CD group. Immunohistochemistry revealed heightened accumulation of lipid/foam cells and CD68-labeled macrophages in the plaques, elevated vascular endothelial growth factor (VEGF), and matrix Metalloproteinase-9 (MMP-9) in the HFD + PLCA group’s plaques, along with reduced collagen and α-SMA-labeled smooth muscle cells, resulting in the highest vulnerability index value. Immunohistofluorescence analysis of frozen plaque sections showed significantly higher SDC-1 expression in the AS mice group compared to the CD group, both positively correlated with plaque vulnerability. Serum analysis demonstrated elevated levels of SDC1, sphingosine 1-phosphate (S1P), and VEGF-A in the AS mice, all positively correlated with plaque vulnerability. Multivariate analysis identified SDC1 as an independent predictor of plaque vulnerability. Conclusion This study enhances our understanding of plaque vulnerability mechanisms and presents SDC1 as a potential biomarker for atherosclerosis. These findings underscore the importance of addressing modifiable risk factors, such as diet and hemodynamics and suggest the utility of serum SDC1 as a valuable clinical marker. Ultimately, these insights may lead to more effective strategies in combating cardiovascular diseases and improving patient outcomes.